2006
DOI: 10.1161/01.str.0000239659.99112.fb
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Atorvastatin Treatment on l -Arginine Cerebrovascular Reactivity and Flow-Mediated Dilatation in Patients With Lacunar Infarctions

Abstract: Background and Purpose-In our study we hypothesized that statins improve endothelial function in patients with lacunar infarctions (LI). Cerebral and systemic endothelial function was determined before and after 3-months treatment with atorvastatin. Methods-Cerebral endothelial function was determined by L-arginine reactivity and systemic endothelial function by flow-mediated dilatation (FMD) in patients with LI (18 patients, aged 61.1Ϯ7.6 years), 20 age-and gender-matched patients with similar risk factors (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
3
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 21 publications
2
76
3
1
Order By: Relevance
“…Recently, a new study made by Pretnar-Oblak et al showed that atorvastatin had improved endothelial functions not only on peripheral arterial system but also on central nervous [14]. The results of our study have shown that treatment with 10 mg atorvastatin daily for a six week period resulted in a statisticaly significant improvement of flow mediated and nitroglycerin induced dilatation in type 2 diabetic patients with average lipid levels.…”
Section: Discussionsupporting
confidence: 61%
“…Recently, a new study made by Pretnar-Oblak et al showed that atorvastatin had improved endothelial functions not only on peripheral arterial system but also on central nervous [14]. The results of our study have shown that treatment with 10 mg atorvastatin daily for a six week period resulted in a statisticaly significant improvement of flow mediated and nitroglycerin induced dilatation in type 2 diabetic patients with average lipid levels.…”
Section: Discussionsupporting
confidence: 61%
“…Most papers excluded patients with carotid stenosis (except 1 30 ), 5 excluded cardiogenic sources of emboli, 32,33,36,38,41 and 3 excluded middle cerebral artery (MCA) stenosis 35,39,40 from the lacunar stroke group.…”
Section: Characteristics Of Included Patients and Control Subjectsmentioning
confidence: 99%
“…30,32,39,40,42 Three studies recruited age-and risk-factor matched control subjects (with longstanding hypertension and hypercholesterolemia in 2 32,34 ; with hypertension only in 1 43 ). Five papers compared patients with lacunar ischemic stroke with patients with cortical ischemic stroke, 35,37,38,42,44 confirming the infarct subtype with CT or MRI.…”
Section: Characteristics Of Included Patients and Control Subjectsmentioning
confidence: 99%
“…Treatment with Atorvastatin has shown an improvement of FMD values in patients with lacunar infarcts and patients with risk factors but without stroke [25]. One study showed than endothelial nitric oxide synthase gene is a modifier of the cerebral response to ischemia [26] and in obese patients the endothelial function is related with thrombolysis [27].…”
Section: Discussionmentioning
confidence: 99%